1981
DOI: 10.1524/ract.1981.28.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Use of Κβ/Κα Intensity Ratios for the Study of Annealing Processes in 51Cr-doped Solids

Abstract: Kß/Ka X ray intensity ratios from the electron capture decay of 51 Cr in S1 Cr (IH)-doped oxyanion salts were determined before and after annealing treatments. The observed change in the ratio is consistent with the overall process: 51 Cr (III) 51 Cr (VI), also inferred from solution analysis of the annealed samples. However, for most samples, the fraction of SI Cr (VI) calculated from the "in situ" analysis was less than that indicated by the solution analysis. No change in the ratio was seen with changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The gure suggests that this ratio is larger for set D, corresponding to the mixed samples of K 2 Cr 2 O 7 + Fe 2 O 3 . This would be in line with the ndings of Collins et al 11 that experimental thin target Kb/Ka intensity Fig. 6 The ratios of the reported and expected Mn concentrations for samples of sets C-D as a function of Cr concentrations.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The gure suggests that this ratio is larger for set D, corresponding to the mixed samples of K 2 Cr 2 O 7 + Fe 2 O 3 . This would be in line with the ndings of Collins et al 11 that experimental thin target Kb/Ka intensity Fig. 6 The ratios of the reported and expected Mn concentrations for samples of sets C-D as a function of Cr concentrations.…”
Section: Resultssupporting
confidence: 87%
“…Large variations exist between reported intensity ratios, probably inuenced by the fact that most of the data have been obtained on thick targets. Only few experiments have been performed on thin targets, one of them by Collins et al, 11 who reported an average Kb/Ka value of 0.1316 for Cr(0), a value of 0.1382 for Cr(III) and 0.1467 for Cr(VI) in measured thin-layer chromium containing samples, which they claimed to be sufficient to distinguish the several oxidation states from the related X-ray spectra. Brunner et al 12 reported relative Kb/Ka intensity ratios between thin Cr metallic and K 2 Cr 2 O 7 samples to be 0.977 AE 0.007.…”
Section: Introductionmentioning
confidence: 99%
“…Using ionization by electron bombardment, Hölzer et al [ 9 ] found that the contribution of this shake process was present throughout the diagram lines. On the other hand, several experiments have been performed to investigate the chemical effect on the intensity ratios for elements [ 10 , 11 , 12 ]. Brunner et al [ 13 ], who used protons as the ionization method, explained their experimental results by a contraction of orbitals due to the charge delocalization of the valence electrons.…”
Section: Introductionmentioning
confidence: 99%